LABORATORY SCALE ELECTROKINETIC REMEDIATION OF HEXAVALENT CHROMIUM FROM CONTAMINATED SOIL - Khalid, M.; Ahmed, N.; Qureshi, R. M. (The Nucleus, 2020)
Pakistan hosts a variety of waste soils around industrial sites located in and around large population centers. Clean up of these waste soils is essential to save potable groundwater reserves beneath these waste soils. Among several waste remediation approaches, the electrokinetic remediation (EKR) technology has fast emerged as a reliable, powerful and highly prominent candidate for effective in situ removal of soluble and leachable toxic species of metals, radionuclides, organics from contaminated soils and water environment. This paper presents results of the first laboratory trial experiment performed at PINSTECH, Islamabad, Pakistan to demonstrate applicability of EKR approach for removal of aqueous phase chromium from silty clay soil around Islamabad. The electroosmotic flow rate was 3.13 ml/hour while the mass balance calculations revealed that the removal efficiency of Cr(VI) was 44.58% for the experimental soil.